Enhancing Psychological Well-Being: Self-Regulated Learning, Motivation, and Emotions Among Doctoral Students in South Africa - Hoque, Muhammad; Singh, Nisha; Shaik, Junaid; Pellissier, RenÃ© (Diversity: Disease Preventive of Research Integrity, 2024)
The likelihood of dropping out and interrupting studies increases with poor psychological well-being (PWB). The promotion of doctoral students' PWB is therefore very important. The aim of this study was to examine how self-regulated learning moderates’ relatedness, intrinsic motivation to learn, and positive emotions in doctoral students at a South African Private Higher Education Institution (PHEI). In this cross-sectional study, 46 doctoral students completed a self-administered anonymous questionnaire using an online platform (QuestionPro). Based on the correlation analysis, relatedness was found to be significantly correlated with intrinsic motivation for learning and self-regulated learning. Self-regulated learning and intrinsic learning motivation were significantly correlated with positive emotion. Regression analysis showed that relatedness was a significant predictor of self-regulated learning. However, self-regulated learning was not a significant predictor of intrinsic learning motivation. Psychological support could be provided to doctoral students by PHEIs through the provision of mental health experts to improve self-regulated learning, relatedness, intrinsic motivation, and positive emotions.